Normalizace endoteliální dysfunkce po transplantaci ledvin je spojena se snížením cirkulujícího visfatinu/NAMPT. Nový marker endoteliálního poškození? - Yilmaz, M. I; Saglam, M; Carrero, J. J (Postgraduální nefrologie, 2010)
Endothelial dysfunction is strongly linked to cardiovascular disease and outcome of patients with chronic kidney disease. We hypothesized that decreased inflammatory activity and increased adiponectin following transplantation could be one mechanism for a better endothelial health. Fifty-eight living donor kidney transplant non-diabetic recipients, 31 (23 male, 29 +/- 5 yr) on cyclosporine A and 27 (10 male, 26 +/- 5 yr) on tacrolimus immunsupression, were studied longitudinally. Visfatin, adiponectin, high sensitive C-reactive protein (hsCRP) levels, brachial artery flow mediated dilatation (FMD) and nitroglycerine mediated dilatation were measured before transplantation and on the 30th and 90th day after transplantation. Pre-transplantation visfatin, adiponectin and FMD values of patients were significantly higher than those of the controls (p < 0.001 for all). All values decreased significantly 30 and 90 d post-transplantation. Plasma visfatin and adiponectin, correlated negatively with FMD levels 90 d both before and after kidney transplantation (p < 0.001 for both). Endothelial function improved during the first month after transplantation, and the degree of improvement correlated to reductions in circulating visfatin, adiponectin and hsCRP levels. Of interest, the intracellular enzyme visfatin was the strongest predictor of FMD both before and after kidney transplantation and may thus reflect endothelial cell damage directly.
Keywords: Kidney Diseases; vazodilatace; Male; biologické markery; longitudinální studie; Immunosuppressive Agents; cévní endotel; Glomerular Filtration Rate; Biomarkers; arteria brachialis; Adult; C-reaktivní protein; dospělí; nemoci ledvin; mužské pohlaví; Endothelium, Vascular; rychlost toku krve; Vasodilation; lidé; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; Nicotinamide Phosphoribosyltransferase; Financing, Organized; Longitudinal Studies; C-Reactive Protein; hodnoty glomerulární filtrace; Female; financování organizované; nikotinamidfosforibosyltransferasa; Brachial Artery; Blood Flow Velocity; imunosupresiva